2020
DOI: 10.3390/w12041158
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating of Potential Climate and Land Use Change Impacts on Floods: A Case Study of the Lower Nam Phong River Basin

Abstract: This study aimed at quantifying the impacts of climate and land use changes on flood damage on different flood occurrences. A Hydrologic Engineering Center’s Hydrologic Modeling System (HEC-HMS) model was calibrated for the period 2005–2011 and validated in the period 2012–2017, and was used to generate hydrographs using rainfall during the period 2020–2039 from CNRM-CM5, IPSL-CM5A-MR, and MPI-ESM-LR climate models under Representative Concentration Pathways (RCPs) 4.5 and 8.5. A Hydrologic Engineering Center’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Panda et al [49] in their study observed that the Mahanadi basin is characterized by a tropical monsoon (June to September) climate and more than 80% of the annual runoff occurs during the monsoon season. Moreover, these high streamflow events or floods [50,51] have a tremendous impact on the local population and ecosystem. Hence, to cope with this obvious impact of floods in the basin area, the study of climate variability impact on river water streamflow has become the need of the hour.…”
Section: Seasonality Of Daily Streamflowmentioning
confidence: 99%
“…Panda et al [49] in their study observed that the Mahanadi basin is characterized by a tropical monsoon (June to September) climate and more than 80% of the annual runoff occurs during the monsoon season. Moreover, these high streamflow events or floods [50,51] have a tremendous impact on the local population and ecosystem. Hence, to cope with this obvious impact of floods in the basin area, the study of climate variability impact on river water streamflow has become the need of the hour.…”
Section: Seasonality Of Daily Streamflowmentioning
confidence: 99%
“…CN III = 23CN II 10 + 0.13CN II (3) where CN I is the runoff curve number value of each LULC type of AMC-I, CN II is the runoff curve number value of each LULC type of AMC-II, and CN III is the runoff curve number value of each LULC type of AMC-III (Table 2). In practice, the three runoff curve numbers of the hydrologic soil group of each LULC type were separately applied to estimate the potential maximum storage under three different AMCs using Equation (4).…”
Section: Suitable Amc For Surface Runoff Estimation Using the Scs-cn Methodsmentioning
confidence: 99%
“…In general, the primary cause of flooding is heavy rainfall [3]. However, many other causes are also due to human activities, such as land degradation; deforestation of catchment areas, urban growth, and increased population along riverbanks [4][5][6]; poor land use planning, zoning, and control of flood plain development; poor drainage, particularly in cities; and insufficient management of discharge from river reservoirs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modeling method relies on Multi-Layer Perceptron (MLP) neural network and Markov Chain (MC), in which the MLP was trained to model land use transitions through creating transition potential maps. The transition potential maps were created based on a set of descriptive environmental variables called drivers, i.e., agricultural areas, distance to urban areas, rivers, roads, as well as altitude, slope, and aspect of land [18]. Thereafter, the Markov Chain method was then applied to process the transition maps for the prediction process [19], based on the past trends of land use changes from 2010 to 2015.…”
Section: Projection Of Future Land Use Changementioning
confidence: 99%